1989
DOI: 10.1152/ajpgi.1989.256.5.g856
|View full text |Cite
|
Sign up to set email alerts
|

EGF content in the gastrointestinal tract of rats: effect of age and fasting/feeding

Abstract: Immunoreactive rat epidermal growth factor (EGF) was measured in the pancreas and in the mucosa and lumen of the stomach, duodenum, jejunum, midjejunum, ileum, and colon of fed or fasted 5- and 12-day-old suckling, and 3- to 4-month-old adult male rats using a homologous radioimmunoassay. The EGF levels in the pancreas in sucklings were lower than in adults and were unaffected by fasting. Both gastrointestinal mucosal and luminal EGF levels were higher in suckling rats than in adults. Fasting caused a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…In the gastrointestinal tract EGF is secreted into the lumen by salivary (Starkey & Orth, 1977) and Brunner's glands (Elder et al, 1978) and has been detected in the luminal contents and mucosa throughout the intestine (Schaudies et al, 1989). Whilst the physiological role of EGF in the adult gut remains unclear, the demonstration of EGF receptors on intestinal epithelial cells (Forgue-Lafitte et al, 1980) indicates that the peptide may be involved in intestinal homeostasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the gastrointestinal tract EGF is secreted into the lumen by salivary (Starkey & Orth, 1977) and Brunner's glands (Elder et al, 1978) and has been detected in the luminal contents and mucosa throughout the intestine (Schaudies et al, 1989). Whilst the physiological role of EGF in the adult gut remains unclear, the demonstration of EGF receptors on intestinal epithelial cells (Forgue-Lafitte et al, 1980) indicates that the peptide may be involved in intestinal homeostasis.…”
mentioning
confidence: 99%
“…Studies involving intravenous administration of large amounts of EGF on a short term basis have resulted in a stimulation of mucosal growth throughout the small and large intestine (Dembinski et al, 1982;Goodlad et al, 1987;Scheving et al, 1980). However, as only small quantities of EGF are normally found in blood (Byyny et al, 1974;Abe et al, 1987) when compared to levels found in the gut lumen (Schaudies et al, 1989) and as it is cleared from the circulation extremely quickly (Jorgensen et al, 1988), luminal administration may be the more relevant approach for such studies. Work in this field has concentrated on the upper gastrointestinal tract using large quantities of EGF and has yielded conflicting results: some workers reported an EGF induced stimulation of mucosal growth (Dembinski et al, 1982;Ulshen et al, 1986), whilst others observed no significant mitogenic response (Goodlad et al, 1987).…”
mentioning
confidence: 99%
“…Both peptides are present in the gastrointestinal tract of suckling and adult rats, but EGF, which is present in milk from several mammalian species including rat milk [47], belongs to the group of milkborne biologically active peptides [48]. EGF levels in the gastrointestinal tract of sucklings are significantly higher than in adults [33] and are dependent on EGF intake [34]. Interestingly, suckling rats fasted overnight or hand fed for 3 days with EGF-free rat milk substitute kept some EGF content in the small intestine (about 15% of the initial level) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated a role for exogenous milkborne EGF in growth and development of the intestine [33,34]. To determine the potential contribution of endogenous EGF, we performed in situ hybridization for EGF mRNA in lZdayold suckling male rats.…”
Section: Egfmentioning
confidence: 99%
“…It was observed that pancreatic weighi and lipase activity were greater in weaned piglets ttrariin suckling ones (Kelly et al 1991). During the suckling period pancreatic fluid and enzyme secretion remained low (Pierz.ynowski et al 1993 EGF ii an important regulator of prenatal and postnatal grornth, affecting both mitogenesis and differentiation of a iariety of cell types (Carpenter and Wahl 1990)' EGF has been ihown to be present in various human tissues such as pancreas, stomach and duodenum (Kasselberg et al' 1985)' it was reported that livers of fasted rats had 40-50% less EGFR thin those of control rats (Freidenberg et al' 1986)' Fasting also caused a significant decrease in levels of EGF of gas'trointestinal tissues in suckling rats but resulted in miiimal changes in adults (Schaudies et al 1989 (Pascall et al 1991) and represents the reverse complement of nucleotide of this sequence.…”
mentioning
confidence: 99%